Persepsi Dosen dan Pegawai Adanya Toxic Culture di Universitas Islam “45” Bekasi - Adi Susila; Yayan Rudianto (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2016)
The development and progress of UNISMA organization which is slow up compared to other universities is caused by the gap between organization culture that is internalized with daily practice in organization. In the formulation from the expert, organization has no strong dominant culture so the culture that is developed is disfunctional culture or also known as toxic culture. With instrument formulated by Gostick & elton (2012), consisted of 14 questions with yes or no answer, the result shows that 1 respondent (1,7%) perceives that there is no problem in existed values in organization. 10 respondents (16,6 %) perceive that there is problem symptom in organization culture that needs to be cautioned and the organization must study to do improvement. And the rest, 49 respondents (81,74%) perceive that is there is gravity in organization culture because the existing culture is disfunctioned (toxic culture) toward organization that needs help from other to fix